DYSTOCIA DUE TO FOETAL HYDROCEPHALUS IN ACCORDANCE WITH ASCITES IN A MULTIPAROUS OSMANABADI GOAT - Sonali Baburao Natkar,; Patil, Anil D; Koli, Anujkumar; Ramteke , Snehal; Surywanshi, Ravi (The Indian Journal of Animal Reproduction, 2024)
A three years old Osmanabadi doe in her fourth parity with a history of kidding two live male kids before 48 hours reporting in the clinic, having continuous straining, with abdominal bloating since night was presented to the Veterinary Clinical Complex, College of Veterinary and Animal Sciences, Udgir. Per vaginal examination revealed that the fetus head was dorsally bulged with half developed cranium, large sized fetus with distended abdomen that fluctuated on pressure. Gross examination of the fetus revealed excessive swelling over the head with accumulation of fluid in the peritoneal cavity. Hence, the case was confirmed as fetal hydrocephalus in accordance with ascites. The doe was treated with parenteral antibiotics, anti-inflammatory, anti-histamines, ecbolics and supportive therapy for 5 days. The case was recovered uneventfully within a week.
Keywords: Ascites; Dystocia; Hydrocephalic; Osmanabadi goat